PENYUSUNAN PROGRAM KERJA ORGANISASI ORANG INDONESIA (Oi) BADAN PENGURUS KABUPATEN INDRAGIRI HILIR BERBASIS SUSTAINABLE DEVELOPMENT GOALS (SDGs) PERIODE 2017-2021 - Agus Rudianto (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
Orang Indonesia (Oi) has been registered in the institution of the unity of nation and politic of Kabupaten Indragiri Hilir num 00-04-04/--56/VIII-2014/PRPJGN/2014 date 27th June 2014. The contribution of Organisasi orang Indonesia (Oi) social organizations of BPK Indragiri Hilir focused on social and environmental field. Such as education assistance for poor children, blood donation, disaster assistance, planting the Mangrove, education assistance and trash problem. SDGs are 17 goals, 169 targets and 241 indicators in social dimension coverage, economic and environment, law and governance. The purpose of this research is to study which indicators of SDGs that can be adopted by Oi BPK Indragiri Hilir in workplan codification. Based on desk review, it can be concluded that the potential one of Indicators of SDGs that can be adopted in Oi Indragiri Hilir workplan are 6 goals, 9 targets and 10 indicators of SDGs which is focused on social and environmental field.